DARK PATTERN DALAM SOCIAL COMMERCE DAN PENGARUHNYA TERHADAP PERILAKU KONSUMEN DIGITAL DI INDONESIA: SEBUAH SYSTEMATIC LITERATURE REVIEW - Muhammadalfansaputra; Roni Zakaria; Yuniaristanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid growth of social commerce platforms in Indonesia, particularly TikTok Shop and Shopee Live, has been accompanied by the increasing use of dark patterns, namely manipulative interface designs intended to influence consumer decisions beyond their conscious awareness. Although dark patterns have been extensively studied in global e-commerce and legal contexts, systematic evidence on how these manipulative designs shape digital consumer behavior within the Indonesian social commerce environment remains limited. This study aims to synthesize and map empirical and conceptual literature on the relationship between dark patterns and digital consumer behavior in social commerce through a Systematic Literature Review guided by the PRISMA 2020 protocol. Literature was identified from Scopus, Google Scholar, and Garuda databases published between 2020 and 2026, using keyword combinations related to dark patterns, social commerce, and consumer behavior. After a four-stage screening process, 27 articles met the inclusion criteria and were analyzed thematically. The findings reveal three dominant dark pattern categories operating in social commerce, namely urgency and scarcity cues, social proof manipulation, and forced continuity mechanisms, which influence consumer behavior primarily through impulsive purchasing, reduced perceived autonomy, and erosion of platform trust, consistent with the Stimulus-Organism-Response framework. The review further identifies a substantial research gap regarding the Indonesian social commerce context, where most existing studies remain descriptive and lack a systematic synthesis grounded in consumer behavior theory. This study contributes a conceptual mapping that can serve as a foundation for future empirical research and for regulatory considerations on consumer protection in Indonesia's digital marketplace.